Non-HDL cholesterol is better than LDL-c at predicting atherosclerotic cardiovascular disease risk factors clustering, even in subjects with near-to-normal triglycerides: A report from a Venezuelan population (2018)
Background: Non-high density lipoprotein cholesterol (non-HDL-c) has emerged as an important tool in primary prevention of atherosclerotic cardiovascular disease (ASCVD), especially among those at high risk. The main objective of this study was to evaluate the predictive value of non-HDL-c for the coexistence aggregation of multiple ASCVD risk factors and compare this with LDL-c in general subjects with normal or near normal triglycerides from Maracaibo city in Venezuela. Methods: This is a descriptive, cross-sectional study with a randomized multistage sampling. 2026 subjects were selected for this study, all were adults ≥18 years old of both genders and inhabitants of Maracaibo city, Venezuela. A complete history and physical medical assessment was performed. A multivariate logistic regression model was used to determine the odds ratio (CI95%) for the coexistence of multiple risk factors for ASCVD. Results: The median (p25-p75) of non-HDL-c was 143 mg/dL (114-174 mg/dL). 52.1% (n=1056) of the sample were women, with a median of 144 mg/dL (115-174 mg/dL) among women and 143 mg/dL (114-17 4mg/dL) among men; p=0.740. Individuals ≥50 years old, smokers, those with hypertension, obesity, diabetes, high waist circumference and elevated hs-C Reactive Protein, all had higher levels of non-HDL-c. A lower median was observed among those <30 years of age with elevated physical activity levels in their leisure time. Non-HDL-c between 130-159 mg/dL (OR=2.44; CI 95%=1.48-4.02; p<0.001) and ≥160 mg/dL (OR=3.28; CI 95%=1.72-6.23; p<0.001) was associated with greater risk of coexistent multiple risk factors for ASCVD, albeit LDL-c was not significant in the multivariate model. Conclusions: Elevated non-HDL-c was associated with conglomeration of multiple risk factors for ASCVD. This suggests evaluation of non-HDL-c may be of better utility in primary care for early identification of subjects for high risk of ASCVD. Future research might focus on the influence of non-HDL-c in cardiovascular mortality.